Students’ Perception of Using Telegram as a Medium During Online Learning - Komang Trisnadewi; Putu Santi Oktarina (Journal of English Language Teaching and Linguistics, 2023)
The online learning policy initially set by the government gradually developed into something of interest because of its flexibility. This development brought telegram, a social media application for sharing messages, to become a medium for online learning. Several researched have been conducted but in a limited scope of discussion. This research seeks to discover students' perceptions of using telegrams as a medium during the learning process, including material, motivation, activeness, learning time, meeting, and teacher's role. This research is essential to contribute information on using technology in education. This descriptive qualitative research involves collecting and analyzing non-numerical data to understand the opinions and experiences of the 3rd-semester students at Hindu State University I Gusti Bagus Sugriwa Denpasar. An online questionnaire that already contained several questions related to the use of telegrams during online discussions was given to the students. The researchers did interviews to crosscheck and follow up on the questionnaire result. The result shows that students positively respond to using telegrams in online learning. However, some students expressed disagreements in several parts, namely motivation, interest, activeness, time of delivery, discussion of the material, and composition. To sum up, Telegrams can be a way to provide learning experiences to students in online learning